Two new species of the genus Mallomonas from the Cat Tien National Park (Viet Nam): Mallomonas distinguenda and Mallomonas skvortsovii - Gusev, Evgeniy S.; Doan-Nhu, Hai; Nguyen-Ngoc, Lam; Kapustin, Dmitry A. (Phytotaxa, 2016)
Mallomonas distinguenda sp. nov. and Mallomonas skvortsovii sp. nov. are described from Dak Lua swamp, located in Cat Tien National Park (Dong Nai Province, Southeastern Viet Nam). The description is based on silica-scale morphology studied by means of transmission and scanning electron microscopy. These species belong to the section Papillosae based on scale morphology. The most characteristic feature for both taxa is the shield reticulation. In the case of Mallomonas distinguenda, it is an external reticulation. By contrast, Mallomonas skvortsovii has internal reticulation.